Monogenic diabetes mellitus in cystic fibrosis. Issue 9 (29th September 2018) - Gan, Hoong-Wei; Bhatt, Jayesh Mahendra; Denvir, Louise; Randell, Tabitha; Sachdev, Pooja
Abstract : We present a non-consanguineous family of three siblings who presented with diabetes mellitus (DM), two of whom had genetically confirmed cystic fibrosis (CF), with one pancreatic-sufficient mutation in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene (ΔF508/R117H;IVS8-5T). A detailed history revealed family members from three successive generations diagnosed with 'type 1' or 'type 2' diabetes, leading to genetic investigations for monogenic DM. A heterozygous frameshift mutation in the hepatocyte nuclear factor 1 homeobox alpha ( HNF1A ) gene (c.404delA) was subsequently confirmed in all three siblings, which is known to cause monogenic diabetes and is exquisitely sensitive to sulfonylurea therapy. Following this diagnosis, both siblings with CF and HNF1A monogenic diabetes were started on gliclazide therapy, while their older brother who had been wrongly diagnosed with type 1 diabetes was switched from insulin to gliclazide, all with excellent therapeutic responses.